Pengaruh Country Of Origin dan Label Halal Terhadap Minat Beli Ulang Konsumen Muslim pada Produk Mi Instan Impor Merek Samyang di Kota Medan - Ramanda, Bima; Dirbawanto, Nana Dyki; Siregar, Onan Marakali; Adlina, Hafiza (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2025)
The dominance of local products has intensified competition in Indonesia’s instant noodle industry, pushing imported brands such as Samyang to innovate in order to attract consumers, including Muslim customers. This study aims to analyze the influence of country of origin and halal label on Muslim consumers’ repurchase intention of imported Samyang instant noodles.The research employed a quantitative method with an associative approach. A total of 96 respondents were selected using purposive sampling. Data were collected through questionnaires and literature studies.The results indicate that both country of origin and halal label significantly influence repurchase intention, both partially and simultaneously. The coefficient of determination shows a moderate strong relationship with R = 0.653. Meanwhile, the adjusted R square value of 39.1% indicates that the two variables contribute to repurchase intention, while the remaining 60.9% is influenced by other factors beyond the scope of this study.